Behaviour of the Foramen Ovale Flow in Fetuses with Intrauterine Growth Restriction - Ângela R. L. Nader; Paulo Zielinsky; Alexandre Antonio Naujorks; Luiz Henrique S. Nicoloso; Antonio Luiz Piccoli Junior; Natássia Miranda Sulis; Luiza Ferreira van der Sand; Victoria de Bittencourt Antunes; Gabriela dos Santos Marinho; Fernanda Greinert dos Santos; Natan Pereira Gosmann; Eduardo Becker Júnior; et al. (Obstetrics and Gynecology International)
Background. Foramen ovale (FO) flow may be altered in IUGR. This study was designed to test this hypothesis. Methods. Forty pregnant women (24–38 weeks) were divided into 3 groups: group I (IUGR), group II (adequate growth and maternal hypertension), and group III (normal controls). Impedance across the FO was assessed by the FO pulsatility index (FOPI): (systolic velocity − presystolic velocity)/mean velocity. Statistical analysis utilized ANOVA, Tukey test, and ROC curves. Results. Mean FOPI in IUGR fetuses (n = 15) was 3.70 ± 0.99 (3.15–4.26); in the group II (n = 12), it was 2.84 ± 0.69 (2.40–3.28), and in the group III (n = 13), it was 2.77 ± 0.44 (2.50–3.04) (p=0.004). FOPI and UtA RI were correlated (r = 0.375, p=0.017), as well as FOPI and UA RI (r = 0.356, p=0.024) and, inversely, FOPI and MCA RI (r = −0.359, p=0.023). Conclusions. The FO flow pulsatility index is increased in fetuses with IUGR, probably as a result of impaired left ventricular diastolic function.